Perceived exertion, time of immersion and physiological correlates in synchronized swimming - Rodriguez-Zamora, L.; Iglesias, X.; Barrero, A.; Chaverri, D.; Irurtia, A.; Erola, P.; Rodriguez, F. A. (International Journal of Sports Medicine, 2014)
This study examined the relationship between ratings of perceived exertion (RPE, CR-10), heart rate (HR), peak blood lactate (Lapeak), and immersion (IM) parameters in 17 elite synchronized swimmers performing 30 solo and duet routines during competition. All were video recorded (50 Hz) and an observational instrument was used to time the IM phases. Differences in the measured variables were tested using a linear mixed-effects model. RPE was 7.7±1.1 and did not differ among routines, and neither did any of the HR parameters. There were differences among routines in Lapeak (F3,7=16.5; P=0.002), number of IM (F3,15=14.0; P<0.001), total time immersed (F3,16=26.6; P<0.001), percentage of time immersed (F3,13=6.5; P=0.007) and number of IM longer than 10 s (F3,19=3.0; P=0.04). RPE correlated positively to HR pre-activation, range of variation and recovery, IM parameters and Lapeak, and inversely to minimum and mean HR. A hierarchical multiple linear regression (MLR) model (number of IM > 10 s, HR recovery, minimum HR, and Lapeak) explained 62% RPE variance (adj. Rm 2=0.62; P<0.001). A stepwise MLR model (Lapeak, mean IM time and pre-exercise HR) explained 46% of performance variance (adj. Rm 2=0.46; P<0.001). Findings highlight the psycho-physical stress imposed by the combination of intense dynamic exercise with repeated and prolonged apnea intervals during SS events.